Transiç\~ao energética para fontes de energia renováveis e sua dependência por minerais críticos: Aspectos geoeconômicos - Fernando Ferreira de Castro; Geraldo Sandoval Góes; Carlos Cesar Peiter; Guilherme Sandoval Góes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The recent transformations and technological innovations in the energy sector have been driven by the urgency of the responses needed to deal with climate change at a global level, to which governments and corporations are committed to achieving goals to reduce their emissions in line with the protocols of production systems and pacts updated annually since the Paris Agreement (2016). Among the main initiatives to achieve these goals is the proposal of energy transition to so-called renewable energy sources, which are emerging as sustainable alternatives that are currently technologically viable and economically attractive for countries, companies and individuals. These clean sources, however, depend on an increase in the mineral production of raw materials that have been considered critical due to their locational rigidity and supply risk, since these materials are present in components and equipment for electricity generation, storage and mobility. In addition, the process of transitioning from traditional high-carbon systems to low-carbon systems tends to have an impact on production chains and the installed infrastructure, which has different levels of dependence and risks associated with changes in the traditional fossil fuel-dependent matrix. The aim of this essay is to bring to light the most emblematic aspects of this discussion, based on an extensive bibliographical review of recent scientific articles and government studies, in order to present the key elements of this debate for understanding the geopolitics of energy in the 21st century.
Keywords: L71; L72; 330; energy transition; renewable energies; critical minerals; green paradox